CONVENTIONAL AND MOLECULAR DETECTION OF PLASMODIUM IN HUMANS - S. N. Panhwar; A. Arijo; M. B. Bhutto; Z. I. Rajput; R. S. Buriro (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2017)
Conventional and molecular detection of plasmodium, causative agent of malaria was carried out, during 2014-15 aiming at comparing the sensitivity of both the protocols. For conventional diagnosis, thin blood smear from 50 malaria suspected victims from Umerkot, Tandojam and adjoining areas were prepared and stained with Romanovisky stain, whereas molecular confirmation on same sample was done by Polymerase Chain Reaction (PCR). For identification of species, restriction enzyme (AluI) analysis of the amplified product was performed. Blood smear examination indicated that 18 (36%) cases were positive with plasmodium parasite, whereas PCR analysis detected plasmodium at 850 base pairs (bps) showing that only 6 (12%) blood samples were infected with plasmodium. When PCR positive samples were subjected to AluI enzyme, the protocols revealed that all victims were positive with Plasmodium falciparum. Comparison of conventional and molecular techniques revealed that 12 (66.60%) false Positive cases were detected by microscopy, whereas PCR assay did not conform to these results. Statistical analysis on the prevalence of malaria reveled non-significant difference from Umerkot and Tandojam at P> 0.05 (X2 = 1.815; P= 0.1779) with 1 degree of freedom (df) whereas PCR results demonstrated significant difference at P< 0.05.